The Definitive Guide to Magento: A Comprehensive Look at Magento - McCombs, Adam (Apress, 2013)
This book has two primary audiences. The first includes website designers and developers looking for an eCommerce solution for clients. Magento can not only be manipulated in terms of design but it can meet some of the most complex development requirements. The second audience includes small to medium-sized business owners who are looking to establish an online eCommerce presence. For most business, Magento is ready to perform right after installation. You can easily configure Magento with very little knowledge of PHP or HTML. Magento also allows you to install themes to modify your store’s appearance. Magento is the ideal eCommerce solution for anyone looking to easily install, customize, and run an online store.